Competence for genetic transformation in Streptococcus pneumoniae: molecular cloning of com, a competence control locus. - Chandler, M S (1987)
To identify and map genes involved in competence for genetic transformation in Streptococcus pneumoniae, we have cloned DNA surrounding an ermB insertion mutation that causes a competence factor deficiency. We recovered the insert and approximately 500 base pairs of neighboring pneumococcal DNA in pMB9. Larger pieces of DNA from this region were unstable in pMB9 and pBR325. However, larger pieces were stable in pKK232-8, an Escherichia coli vector containing strong transcription terminators. Overlapping pieces of wild-type DNA from this competence control region were cloned and mapped in this vector. Insertion mutations were constructed in vitro throughout the cloned region. When crossed into the pneumococcus chromosome, they showed that the com locus was 4.2 to 5.2 kilobases long.